Efficient Transmission of Mixed Plasmodium falciparum/vivax Infections From Humans to Mosquitoes. (24th September 2019) - Balasubramanian, Sujata; Rahman, Rifat S; Lon, Chanthap; Parobek, Christian; Ubalee, Ratawan; Hathaway, Nicholas; Kuntawunginn, Worachet; My, Mok; Vy, Dav; Saxe, Jeremy; Lanteri, Charlotte; Lin, Feng-Chang; et al.
Abstract: Background: In Southeast Asia, people are often coinfected with different species of malaria ( Plasmodium falciparum [ Pf ] and Plasmodium vivax [ Pv ]) as well as with multiple clones of the same species. Whether particular species or clones within mixed infections are more readily transmitted to mosquitoes remains unknown. Methods: Laboratory-reared Anopheles dirus were fed on blood from 119 Pf -infected Cambodian adults, with 5950 dissected to evaluate for transmitted infection. Among 12 persons who infected mosquitoes, polymerase chain reaction and amplicon deep sequencing were used to track species and clone-specific transmission to mosquitoes. Results: Seven of 12 persons that infected mosquitoes harbored mixed Pf/Pv infection. Among these 7 persons, all transmitted Pv with 2 transmitting both Pf and Pv, leading to Pf/Pv coinfection in 21% of infected mosquitoes. Up to 4 clones of each species were detected within persons. Shifts in clone frequency were detected during transmission. However, in general, all parasite clones in humans were transmitted to mosquitoes, with individual mosquitoes frequently carrying multiple transmitted clones. Conclusions: Malaria diversity in human hosts was maintained in the parasite populations recovered from mosquitoes fed on their blood. However, in persons with mixed Pf/Pv malaria, Pv appears to be transmitted more readily, in association with more prevalent patent gametocytemia.